2017
DOI: 10.18632/oncotarget.22478
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic index to predict pulmonary metastasis of giant cell tumor of bone

Abstract: PurposeGiant cell tumor of bone (GCTB) is an intermittent tumor with a low probability of pulmonary metastasis. Our aim was to investigate the risk factors and establish a nomogram predictive model for GCTB pulmonary metastasis.MethodsWe retrospectively evaluated GCTB patients at our center from 1991 to 2014. The cohort was randomized into training and validation sets. Univariate and multivariate analyses were used to evaluate the risk factors of pulmonary metastasis. A nomogram was established. Internal valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The course of GCTB pulmonary metastasis is unpredictable. 6,7,61,64,65 Spontaneous resolution has been reported, 18,66,67 as was the case in two patients in this series. Due to the usual benign indolent course and the controversial management of such nodules, 15,17,6770 histopathological confirmation was not obtained routinely especially with small and inaccessible nodules.…”
Section: Discussionsupporting
confidence: 66%
“…The course of GCTB pulmonary metastasis is unpredictable. 6,7,61,64,65 Spontaneous resolution has been reported, 18,66,67 as was the case in two patients in this series. Due to the usual benign indolent course and the controversial management of such nodules, 15,17,6770 histopathological confirmation was not obtained routinely especially with small and inaccessible nodules.…”
Section: Discussionsupporting
confidence: 66%
“…Lung metastases occur in 1-9% of patients with GCTBs [5][6][7][8][9]. Distal radius [8,9], Campanacci stage 3 [114], and repeated local recurrences [114][115][116][117][118][119] have been associated with lung metastases. A recent study including patients with GCTB of the extremities reported similar lung metastasis rates between the group undergoing surgery and preoperative and postoperative denosumab therapy and the group undergoing surgery alone (3.3% (1 of 30 patients) vs. 4.7% (18 of 381 patients)) [115].…”
Section: Lung Metastasismentioning
confidence: 99%
“…The multivariate Cox regression suggested that higher T stage was one of the prognostic factors. Tumor size as the independent risk factor for lung metastasis was previously found [18]. Based on the Campanacci classification, which has been widely accepted in evaluating giant cell tumor, grade III represented the aggressive type.…”
Section: Discussionmentioning
confidence: 97%